PENGARUH LEVERAGE, PROFITABILITAS, DAN KEPEMILIKAN MANAJEMEN PADA CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE PERUSAHAAN PERTAMBANGAN - Prakasa, Sila; Putra Astika, Ida Bagus (E-Jurnal Akuntansi, 2017)
This research aims to obtain empirical evidence of the influence of leverage, profitability, management and ownership on CSR disclosure mining company. CSR disclosure can be seen on the social responsibility report contained in the company's annual report. Measurement of CSR disclosure index with Global Reporting Initiative Generation 3.1 (GRI G 3.1). Data collection methods used in this study was a nonparticipant observation by multiple linear regression analysis technique. This research was conducted on the mining companies were listed on the Indonesia stock exchange period 2011-2014. The sample was selected using a purposive sampling and retrieved 40 data already meets the criteria of a sample. The research results showed that profitability and ownership management has positive influence on CSR disclosure mining companies listed on the Indonesia stock exchange period 2011-2014.
Keywords: CSR , CSR disclosure, Global Reporting Initiative